Implementation Smart Automatic Transfer Switch Multi-Input Multi-Output (MIMO) On DC House - Wildan Surya Wijaya; Sagita Rochman; Adi Winarno; Aditya Ilham; Mohamad Ilham (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2025)
In the development of technology, the specialization in New and Renewable Energy (NRE) is increasing, this is supported by the infrastructure of using NRE as a need for transportation of electric cars, electric bicycles, electric vehicle charging stations, home electricity needs, and the fulfillment of industrial needs. The electrical basis of the system is DC electricity where it is more efficient because there is no need to convert to AC electricity. In this study, it supports the transition and full use of DC electrical energy with an ATS system with various sources and equipped with a variable output of DC voltage used. The test results showed that the solar panels performed optimally at a voltage of 13.4 V and a current of 0.8 A, while the wind turbine had a fluctuating performance with a voltage between 7.2 V to 14.2 V and a current of 0.21 A to 0.5 A. Picohydro had a stable voltage in the range of 11.4 V to 13.2 V, but the current was low due to limited water flow. PSUs, as a backup power source, show stable performance with voltages between 14.3 V to 14.5 V and currents of 1.05 A to 1.3 A. MIMO ATS (Automatic Transfer Switch) systems are proven to be able to prioritize resource priorities to maintain power stability.